Find the general solution of y"+9y=(t^2)(e^3t)+6.

r^2+9=0

r=±3*i*

Answer: c_{1}cos 3t+c_{2}sin 3t+(1/162)(9t^2-6t+1)e^(3t)+2/3

Please show the work step by step.

Find the general solution of y"+9y=(t^2)(e^3t)+6.

r^2+9=0

r=±3*i*

Answer: c_{1}cos 3t+c_{2}sin 3t+(1/162)(9t^2-6t+1)e^(3t)+2/3

Please show the work step by step.

Tutors, sign in to answer this question.

Grigori S. | Certified Physics and Math Teacher G.S.Certified Physics and Math Teacher G.S.

The general solution(y_{0}) of your homogeneous equation y" + 9y = 0 is

y_{0} = C_{1}sin3t + C_{2} cos 3t (because, as you have already noticed, r = ±3i ) (1)

(we have discussed it several times in the past).

To find a particular solution for the inhomogeneous equation let' s rewrite it in the following way:

y" + 9y - 6 = t^{2}e^{3t} (2)

If we introduce a new variable z = y - 2/3 we can write

z" + 9z = t^{2}e^{3t} (3)

We are going to look for a particular solution for (3). Then a particular solution for y will be

y_{1} = z + 2/3 (4)

Because the right side of the equation (3) is t^{2} e^{3t} we can look for the solution in the form

z = e^{3t} (at^{2} +bt + c) (5) (quadratic expression times exponenet)

Substitute (5) into (3). You will obtain:

e^{3t}[ 9at^{2} + (6a + 9b)t + 3b +9c +6at +2a +3b] + 9e^{3t} (at^{2} +bt +c) = t^{2} e^{3t}

Now cancel alll terms by e^{3t}. It gives you

18at^{2} + (12a + 18b(t + (2a +6b + 18c) = t^{2} (6)

To make both sides of the equation (6) equal, we have to put

18a = 1

12a + 18b = 0

2a + 6b + 18c = 0

Solve the system and you will come up with answers: a = 1/18, b = -1/27 and c = 1/162. Thus

z = e^{3t}( t^{2}/18 - t/27 +1/162) = e^{3t}(9t^{2} - 6t +1)/162

and

y = y_{0} + z + 2/3 = C_{1} sin(3t) + C_{2} cos (3t) + e^{3t}(9t^{2} - 6t +1)/162 + 2/3 (general solution).

If you need more details let me know. Good luck!

r=±3i

Homogenerous solution: y_{o} = c1cos 3t+c2sin 3t

Let y* = (At^2+Bt+C)e^3t + 6/9 be a particular solution. Plugging into the original equation,

y*' = [3(At^2+Bt+C) + 2At + B] e^3t

y*'' = [9(At^2+Bt+C) + 3(2At + B) + 3(2At+B) + 2A] e^3t

y*"+9y* = (t^2)(e^3t)+6 becomes

[18(At^2+Bt+C) + 3(2At + B) + 3(2At+B) + 2A] e^3t = (t^2)(e^3t)

Comparing coefficients:

t^2: 18A = 1 => A = 1/18

t: 18B+12A = 0 => B = -(2/3)(1/18) = -1/27

t^0: 18C+6B+2A = 0 => C = -(1/3)B - (1/9)A = 1/81 - 1/162 = 1/162

So, the general solution is

y = y_{o} + y* = c1cos 3t+c2sin 3t+(1/162)(9t^2-6t+1)e^(3t)+2/3 <==Answer

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.